If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x+7)=6(-4)
We simplify the equation to the form, which is simple to understand
8(x+7)=6(-4)
Reorder the terms in parentheses
+(+8x+56)=6*(-4)
Remove unnecessary parentheses
+8x+56=+6+*(-4+)
Reorder the terms in parentheses
+8x+56=+(-24)
Remove unnecessary parentheses
+8x+56=-24
We move all terms containing x to the left and all other terms to the right.
+8x=-24-56
We simplify left and right side of the equation.
+8x=-80
We divide both sides of the equation by 8 to get x.
x=-10
| log(6x+2)=1+log(x-3) | | 2(l+5w)=42 | | 0.12xY=1.2 | | 2580+2920+x=3000.3 | | 4[v-5]=16 | | 36+-4k=-64+-24k | | [c+3]=15 | | -5x-19=-13x | | 45n+7776=75 | | Hg(x)=3.08(120)sqrt+18.97 | | 10x=6.5 | | 57.95=50.45+60 | | 3n^2-10n+5=0 | | 3a+6=-10 | | 3n^2-10+5=0 | | 5(3x+5)=160 | | .3m=12 | | 7.6+-5(0.1+1.1)=1.6 | | 5x+14=2p | | Hg(x)=3.08(90)sqrt+18.97 | | 4(y+2)=10(5y) | | 1+2b+12=5b-2 | | 36-4k=-8(3k+8) | | 5+-8=-18 | | 48*4.0%*0.075/130-4*0.015= | | (X-2)(x-2)-12=0 | | 77x^2+54x+9=0 | | P-11=4.2 | | 3x-0.5y=-6.8 | | -0=-5n-2n | | -10x^2+0x+10=0 | | 2*3+x=5+x |